2020
DOI: 10.3389/fpubh.2020.00169
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Evaluation of the Pain Management VA-ECHO Program Using the RE-AIM Framework: The Participant's Perspective

Abstract: Introduction: Veterans frequently seek chronic pain care from their primary care providers (PCPs) who may not be adequately trained to provide pain management. To address this issue the Veterans Health Administration (VHA) Office of Specialty Care adopted the Specialty Care Access Network Extension for Community Healthcare Outcomes (VA-ECHO née SCAN-ECHO). The VA-ECHO program offered training and mentoring by specialists to PCPs and their staff. VA-ECHO included virtual sessions where expertise was shared in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 21 publications
0
19
1
Order By: Relevance
“…A study of Veterans Affairs ECHO Chronic Pain program found that many participants perceived a sense of community that developed throughout the program, which helped them to face the challenges of managing an uncurable, debilitating chronic health condition. 26 Other models geared at creating a community of practice also report that such management approach to chronic pain leads to improved clinicians' confidence in their ability to manage pain and communication skills. 25,26 In line with results from other Project ECHO programs, most of the identified challenges were related to inherent characteristics of existing treatment models.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A study of Veterans Affairs ECHO Chronic Pain program found that many participants perceived a sense of community that developed throughout the program, which helped them to face the challenges of managing an uncurable, debilitating chronic health condition. 26 Other models geared at creating a community of practice also report that such management approach to chronic pain leads to improved clinicians' confidence in their ability to manage pain and communication skills. 25,26 In line with results from other Project ECHO programs, most of the identified challenges were related to inherent characteristics of existing treatment models.…”
Section: Discussionmentioning
confidence: 99%
“…26 Other models geared at creating a community of practice also report that such management approach to chronic pain leads to improved clinicians' confidence in their ability to manage pain and communication skills. 25,26 In line with results from other Project ECHO programs, most of the identified challenges were related to inherent characteristics of existing treatment models. For example, Moeckli and colleagues 46 found that when multidisciplinary or interdisciplinary settings are not in place, it might be difficult for ECHO programs to alter traditional, one-dimensional patterns of care in primary settings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations